Interference of vaccinal antibodies on serological diagnostic of leptospirosis in vaccinated buffalo using two types of commercial vaccines - de Nardi Júnior, Geraldo; Jorge, André Mendes [UNESP]; Ribeiro, Márcio Garcia [UNESP] (My University, 2013)
The vaccinal antibodies interference represents one of the problems in the leptospirosis diagnostic on serum. The present study aimed to determine the pattern of serum agglutinins anti- Leptospirae spp in vaccinated female buffaloes against leptospirosis using two types of commercial vaccines: bacterin and extern membrane. The temporal interference of vaccinal titers on serum diagnostic was evaluated. Three groups of 11 adult female buffaloes were established as follows: G1 control, non-vaccinated; G2: vaccinated with bacterin containing six serovars and G3 with extern membrane vaccine containing five serovars. A booster was administered at 30 days from the first vaccination (dfv) and two re- vaccinations were performed in each semester (days 210 and 390). Serum samples were collected on days 0, 15, 30, 45 and 60 and every 30 days until 540 dfv, being submitted to Serum Agglutination Microscopy (SAM) against the serovars present in the vaccine. G1 remained always negative. Both vaccines induced serologic responses when assessed by SAM at 150 days post first vaccination against all serovars and they revealed maximum titers around days 45 and 60 after first vaccination. At the re-vaccination there was an increase on agglutinin levels, but of less intensity than the levels previously observed. After six months from the second revaccination (540 dfv), they were almost zero, which demonstrates the short duration of diagnostic interference. The serologic monitoring of the vaccinated herds can be an efficient method to evaluate the status of protection provided by the vaccine.
Keywords: Buffalo; Leptospirosis; Serodiagnosis; Vaccination